COMBING ABILITY OF CMS AND RESTORERS IN RICE (O. sativa L.) (Bangladesh Journal of Plant Breeding and Genetics, 2013)
General and specific combining ability effects were estimated from a 5 line × 8 tester crosses to explore the genetic behavior of CMS and restorers in rice. The variance for GCA and SCA showed predominance of non-additive gene action for all the ten morpho-physiological traits. The estimates of GCA effects revealed that none of the parent was general combiner for all the traits in desired direction. Gan46A and BR827R were good general combiners for higher grain yield coupled with earliness, and IR46R and BR168R was good general combiner for grain yield and lateness in maturity. Good x poor general combiners (Gan46A × Gui99R) for grain yield produced the best specific cross for higher grain yield coupled with earliness, longer panicle, panicles/plant, filled grains/panicle and less sterility (%). Additive × additive, additive × dominance and dominance × dominance gene interactions were involved in deriving good specific cross for grain yield.DOI: http://dx.doi.org/10.3329/bjpbg.v20i1.17013